Family functioning and resilience in students with outstanding powers of the junior year of a public educational institution with high academic standards during the period 2013 - García Pérez, Teófilo Josué (2019)
Objective: In this research the relationship between resilience and family functioning is analyzed in a sampleof 231 students of the third year of secondary sections of an educational institution publish with high academicstandards. Material and Methods: assessing variable resilience resilience Scale was used Young (1993) and forthe variable family Functioning Assessment Questionnaire family Functioning (Ceff ) produced by Atri (2006 )which is developed based on the McMaster model of Family Functioning (MMFF ). Results. The results showa significant relationship between the dimensions of resilience and family functioning. It was determined thatstudents who come from homes with married parents describe their family as functional and have a high level ofresilience. Conclusions: This supports the theoretical considerations to consider family functioning as influentialand instrumental in the formation of the resilience factor